INNOVATIVE METHODS FOR TEACHING AS A FOREIGN LANGUAGE (International journal of artificial intelligence, 2024)
This article explores the evolution of English as a Foreign Language (EFL) teaching methodologies, highlighting the shift from traditional, teacher-centric approaches to student-centered, technology-integrated, and learner-driven methods. It examines innovative techniques that enhance engagement, personalize learning, and cater to diverse learning styles, ultimately fostering effective language acquisition.